Earth observation and navigation satellite technology: applications and economic benefits - Najeeb M.I.; Syamsir A.; Abu Bakar M.S.; Khan T. (Elsevier, 2025)
Artificial satellites are essential for telecommunications, broadcasting services, weather forecasts, and navigation even in remote regions. Apart from keeping an eye on potential threats to crops, including drought and insect infestation, satellites are also useful in detecting and monitoring raging wildfires, emerging storms, rising floods, and other potential disasters of catastrophic proportions. The satellite industry is poised to boost economic growth as it opens the path to new markets and job opportunities despite global economic uncertainties. This article explores recent developments in Earth observation and navigation satellites and their applications in enhancing the capabilities of agencies and industries. Apart from highlighting the challenges faced, the article also sheds some light on promising areas for the future development of satellite technology and the space economy. The chapter also touches on economic benefits stemming from the widespread utilization of satellite technology applications. ? 2025 Elsevier Inc. All rights reserved.